Mortal Kiss : Fool's Silver - Moss, Alice (London Bantam Books, 2011)
"When smouldering Finn and sexy Lucas arrive in Winter Mill, life starts to get very complicated for Faye McCarron. But two boys battling for her heart is just the start; events in town are turning sinister. There's a dead body in the woods, a motorcycle gang on the prowl, and the snow just won't stop falling. Something evil is at work, and only Faye and best friend Liz can stop it. As the temperature drops and the nights draw in towards Hallowe'en, they must uncover the dark secret at the heart of Winter mill --before it's too late"--
Keywords: Fiction -- Werewolves